Trends of Dengue Disease Epidemiology. Issue 1 (10th March 2017) - Cucunawangsih,; Lugito, Nata Pratama Hardjo
Dengue disease is an emerging mosquito-borne viral infection transmitted between humans by Aedes spp. that are distributed mainly in the tropical and subtropical region along with chikungunya and zika diseases. The distribution of dengue disease is influenced by local variation, such as geography, rainfall, temperature, and rapid urbanization or migration. The epidemy of mosquito-borne infection significantly led to increased number of cases and hyperendemicity which induce a more severe form of dengue accompanied by cocirculation of chikungunya and zika. The rapid global spreading of dengue disease created public health burdens that are presently unfulfilled by the absence of specific therapy, simple diagnosis tool for the early phase, and effective and efficient vector control system. This review highlights the current situation of dengue distribution, epidemiology, and new strategies for early dengue diagnosis and risk prediction of severity that can be used to improve oversight and alleviate the heavy burden of the disease.